ORALLY DISINTEGRATING TABLET MELOXICAM FORMULATION WITH VARIATION CONCENTRATION OF AC-DI-SOL® AND KOLLIDON CL® AS SUPERDISINTEGRANT AGENT - Angi Nadya Bestari; T.N. Saifullah Sulaiman; Abdul Rohman (Majalah Farmaseutik, 2016)
Meloxicam is one of the most commonly prescribed anti-inflammatory drugs which is widely consumed by elderly patients. Meanwhile, elderly patients often have difficulty in consuming conventional tablets. Orally disintegrating tablet (ODT) is a solid dosage form that quickly dissolves when placed on the tongue and is expected to be the solution for patients who have difficulty consuming conventional tablets. The research aimed to formulate ODT meloxicam with a variation of superdisintegrant agent, Ac-Di-Sol and Kollidon CL, and obtain the superdisintegrant agent composition of the optimum formula. ODT contained 7,5 mg meloxicam as the active ingredient and excipients were included of Ac-Di-Sol and Kollidon CL as superdisintegrant agent, Avicel PH 102 as a filler binder, and magnesium stearate and talcum as a lubricant. Design Expert 7.1.5 software helped to determine the formula and optimum formula based on the composition of superdisintegrant agent, Ac-Di-Sol and Kollidon CL. ODT was made by direct compression method and was evaluated its physical properties of granul and tablet. The data then compared with the literature and analyzed later to get the optimum formula. The results showed that Kollidon CL could accelerate the disintegration time, while Ac-Di-Sol prolonged the disintegration time of ODT. The formula which consists of 4,5 mg Ac-Di-Sol and 10,5 mg Kollidon CL had DE60 93,12%. The optimum formula consisted of 5,4 mg Ac-Di-Sol and 9,6 mg Kollidon CL which resulted in 4,1 kg hardness response, 0,47% friability, 23 seconds disintegration time, and 19 seconds wetting time.